URGENSI MAPPANDE MANUQ SEBAGAI NAFKAH PRA-NIKAH DALAM PERNIKAHAN MASYARAKAT MANDAR PERSPEKTIF HUKUM ISLAM - Suharna Ismail; Shalsabila Maharani; Khaerul Yakin; Malik Fajar; Riyad Adriyan (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to examine the urgency of Mappande manuq as a premarital practice in Mandar custom and analyze its position from an Islamic law perspective, in order to provide a comprehensive understanding of the limits of custom in the implementation of marriage. This study is field research with a qualitative approach. The primary data sources in this study are the community in Beru-beru Village, Kalukku District, Mamuju Regency, while the secondary data sources are books, journals, and articles related to this study. The data collection techniques used in this study are observation and interviews. From the results of the study, there are two main points to be discussed, namely the concept of nafkah in Islam and the concept and urgency of Mappande manuq as pre-marital nafkah. The results of this study are expected to contribute to a better understanding of the urgency of Mappande manuq as pre-marital nafkah in Mandar marriages, especially from the perspective of Islamic law.